Pergeseran Bahasa Muna dalam Ranah Pendidikan di Kabupaten Banggai - Siti Fatinah; NFN Tamrin (Balai Bahasa Sulawesi Tengah, 2021)
This research is aimed to describe the pattern of language shifts of Muna Language (BM) in the education domain in the Banggai Regency and explain the factors that caused those shifts. The research data was obtained using the speaking and listening method through questionnaire, interview, note-taking, and participating observation techniques. Quantitative data were processed using descriptive statistics (calculated the mean). There are four categories used to interpret the BM shift patterns, namely not yet shifted; begins to shift, but tends to persist; begins to shift; has shifted. The result of the study indicated that the shift in BM in the education aspect in the Banggai Regency, both based on age, gender, education, and occupation, showed a varied pattern of language shift. Based on age group, age 11-15 years old, BM has shifted (always use BI); 16-27 and 28-49 years, BM starts to shift (uses BI more often), and 50 years and over, BM has not shifted persists. Based on gender, both male and female, the pattern of shifting in BM are almost the same, namely starting to shift. Based on the education category, the pattern of BM shift varies: SD/TTSD BM begins to shift, but tends to persist; in SMP, SMA, and PT, BM began to shift (using BI more often). Varied patterns of BM shifts are also seen in the job category. Muna people, who are also a student, BM has shifted (always using BI); Civil servants/TNI/Polri and private employees, BM began to shift (using BI more often); self-employment, trading, and other occupations, BM began to shift, but tended to persist; farmers, have not shifted persist (using BM and BI in a balanced way). The shift in BM in the domain of education is caused by several factors, including social factors, where the Muna people live, ethnic diversity, ethnic minorities, and bilingualism. Among these factors, social factors, bilingualism, ethnic minorities, and where the Muna people live are very dominant in influencing the shift in BM in the education domain in the Banggai Regency.